2002
DOI: 10.1007/s00415-002-1311-2
|View full text |Cite
|
Sign up to set email alerts
|

Practical importance of neuroprotection in Parkinson's disease

Abstract: Consensus could be reached that there is overwhelming evidence of preclinical neuroprotection. However, the evidence of neuroprotection/neurorescue under clinical conditions is limited. Lessons from clinical trials designed to show neuroprotection (selegiline, amantadine, dopamine agonists) demonstrate that with the drugs available neuroprotection/neurorescue has to start as early as possible. A PET-controlled clinical trial with ropinirole shows that there seems to be a good chance for neuroprotection in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Hence, there is a need to develop new treatments aimed at stopping or slowing down the pathological process (Riederer et al, 2002;Schapira, 2009). Indeed, there have been many studies over the years-mainly in animal models of the disease-reporting that some substances or treatments (e.g., deep brain stimulation; Wallace et al, 2007), save or neuroprotect the dopaminergic system in parkinsonian cases.…”
mentioning
confidence: 99%
“…Hence, there is a need to develop new treatments aimed at stopping or slowing down the pathological process (Riederer et al, 2002;Schapira, 2009). Indeed, there have been many studies over the years-mainly in animal models of the disease-reporting that some substances or treatments (e.g., deep brain stimulation; Wallace et al, 2007), save or neuroprotect the dopaminergic system in parkinsonian cases.…”
mentioning
confidence: 99%
“…This is most surprising, because a retrospective study demonstrated that in the decade before onset of classic motor symptoms, PD patients consult their general practitioners (GPs) an average of 5.9 times, which is more than twice as often as age‐matched persons without PD 6. Some progress has been made toward the development of neuroprotective therapies for PD, and encouraging results from clinical trials have been summarized recently 7. Clinical studies aimed at evaluating neuroprotective therapies in humans, however, are unfortunately limited by the rarity in specialized centers of untreated patients in early stages of their disease,7 which is particularly true for atypical Parkinson syndromes.…”
mentioning
confidence: 99%
“…In addition, there is little evidence that neuroprotective therapies are useful in the clinical setting [108].…”
Section: Expert Opinionmentioning
confidence: 99%